Myelopathy due to bilateral symmetrical dumbbell cervical ganglioneuroma in a pediatric neurofibromatosis type 1 patient and rigid posterior instrumentation-a case report - Hergunsel, Omer Batu; Demir, Fatih; Akin, Mehmet Mustafa; Kaplan, Metin (Springernature, 2019)
Background Although neurofibromatosis type 1 (NF1) is a common genetical disorder, symptoms due to neural involvement are rare among infants and children. Ganglioneuromas are slow-growing tumors and can be seen in patients with NF1. However, bilateral symmetrical involvement is very rarely reported in the literature. We present a rare pediatric case with NF1 who presented with upper cervical bilateral symmetrical ganglioneuroma. Case presentation A 7-year-old male presented with progressive gait disturbance, falls, and bilateral limb and trunk numbness that started several weeks ago. Physical examination revealed generalized cafe au lait spots, neurofibromas, and axillary and inguinal freckling. Family history for NF1 was positive. Neurological examination showed slight paraparesis and hypoesthesia of the upper extremities with C4-C5 dermatomas being more distinct. Cervical magnetic resonance imaging (MRI) revealed contrast enhancing dumbbell-shaped symmetrical lesions originating from both C3 nerve roots extending to C2-C5 vertebral body levels. There was a significant spinal cord compression causing myelopathy as well as dystrophic changes and kyphotic deformity at those levels. The patient was operated and the lesions were totally excised via C2-3-4 laminoplasty. Histopathological evaluation reported the lesion as ganglioneuroma. Following the surgery for excision of the lesions, the patient presented with rapidly progressing kyphotic deformity and underwent rigid craniocervical fusion. Conclusion Ganglioneuromas are seen among children, tend to occur in the mediastinum, abdomen, and retroperitoneal area, and may accompany NF1. Cervical spinal ganglioneuroma, however, is a very rare entity. Co-existence of NF1 and bilateral symmetrical cervical ganglioneuroma is highly unusual. Like neurofibromas, ganglioneuromas are slow-growing tumors and therefore they are not expected to cause myelopathy and related symptoms during childhood. Symmetrical nature of the lesions results in myelopathy and early onset of symptoms. Due to the risk of postoperative increase of kyphotic angulation, laminoplasty should be considered. Although laminoplasty alone does not prevent the progression of kyphotic changes, the procedure may allow the use of sublaminar wires and laminar hooks for future surgeries to correct the deformity.
Keywords: Neurofibromatosis type 1; Ganglioneuroma; Laminoplasty; Craniocervical fusion